Production Performance of Debu and Kelabu Sentul Chicken at Different Igy Concentrations - A. U. Khairiyah; C. Sumantri; S. Murtini; A. Anang (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2023)
Sentul chicken is one of Indonesia’s native chickens that has high potential for meat and egg production performance. The production of Sentul chicken breeds with high body resistance is one of the solutions to fulfill this potential. This research aimed to ascertain the impact of various IgY concentrations (high, medium, and low) on the production of 90 Debu and 90 Kelabu Sentul chickens. Parameters observed included pre-laying and laying performance. Six replications of a completely randomized design were used to conduct the experiment. The Anova test was used to analyze the data that was collected. The findings revealed that different strains and sex of Debu and Kelabu Sentul chickens did not significantly affect the value of IgY concentration. In the entire population studied, only 12.09% of Debu Sentul chickens and 11. 32% of Kelabu Sentul chickens had low Igy concentration values. In pre-laying period, the difference in the types of chicken strains has no significant effect on the body weight gain and thefeed convertion. Chickens with high IgY concentrations performed worse during the laying phase than hens with low IgY concentrations. The research found that the population of Kelabu Sentul chickens with high IgY concentration value is more than Debu Sentul chickens, which makes them suitable to be used as breeders.